KESESUAIAN LOKASI DAN JANGKAUAN PENCEMARAN INDUSTRI DI KECAMATAN SAYUNG, KABUPATEN DEMAK - Renny Desiana; Bitta Pigawati (Jurusan Perencanaan Wilayah dan Kota, 2018)
Industrial development is always offset by an increase in quality of life. Development from the industrial sector that is not controlled can affect the increase in environmental pollution. Research to assess the suitability of industrial location and levels of industrial pollution on case studies in Sayung Subdistrict, Demak was conducted. This study used quantitative approach method. Analytical technique were performed by identification and weighting. Spatial analysis was conducted with Geographic Information Systems (GIS) and analysis of public perceptions was presented using a quantitative description. The analysis wase the identification of Sayung district condition, land suitability of industrial location and the level of industrial pollution. The results of the analysis showed that the location with